Association of National Area Deprivation Index with dietary patterns and pain-related inflammatory biomarkers in community-dwelling adults with chronic low back pain - Strath, Larissa J.; Dembowski, Jonas G.; Tamargo, Javier A.; Sims, Andrew M.; Overstreet, Demario S.; Penn, Terence M.; Bakshi, Rahm J.; Bajaj, Eeshaan; Quinn, Tammie L.; Long, D. Leann; Sorge, Robert E.; Goodin, Burel R. (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionChronic low back pain (cLBP) is a common health condition associated with substantial personal and economic costs. Recent literature suggests that socioeconomic status (SES) and diet quality may influence its impact.MethodsThe purpose of this study was to examine whether SES, measured via the National Area Deprivation Index (NADI), and diet quality, assessed by the dietary inflammatory index (DII), were associated with proinflammatory cytokine levels and movement-evoked pain outcomes in individuals with cLBP. We hypothesized that individuals with cLBP with lower NADI and DII scores would exhibit significantly greater pain and higher levels of inflammatory biomarkers. Participants with cLBP (n = 78) completed questionnaires assessing pain and demographic factors, along with a 24 h food recall. Inflammatory biomarkers were measured from peripheral blood samples collected prior to the completion of the questionnaires.ResultsAnalyses revealed that NADI and DII were associated with a similar profile of inflammatory biomarkers and pain outcomes and that DII varied as a function of NADI.ConclusionsThese findings offer important information for future targeting goals for treating vulnerable populations with cLBP. Future studies are warranted to determine whether the relationships among SES, diet quality, and inflammation extend to other chronic pain conditions.